Model Green Logistik Pada Proses Industri Dan Penggunaan Produk (LPPU) Di Industri Semen Untuk Menurunkan Emisi Karbon Dioksida - Noviansyah, Denny; Mada, Danie Hayam; Sholihah, Sita Aniisah; Arifa’i, Achmad Muhyidin; Yasir, Angel Farahnia (Institut Transportasi dan Logistik Trisakti, 2024)
In the current development of globalization, one of the industrial sectors that continues to grow every year is the cement industry because cement is the main material in the construction process. Research institutions state that cement contributes around 8% of the world's carbon dioxide (CO2) emissions and the largest comes from industrial processes and product use (IPPU) so that the concept of environmentally friendly logistics can be implemented to reduce CO2 emissions. This study uses the Dynamic System method. The results of the study show that the use of alternative raw materials and alternative fuels can reduce CO2 emissions generated from the cement production process. This is evidenced by the results of the first scenario, namely Business as Usual, which is 334.90 KgCO2, then decreased by 38.2% or to 207.02 KgCO2 in the second scenario, namely the use of alternative raw materials, and in the third scenario, namely the use of alternative fuels, it also decreased by 68.9% or to 100.88 KgCO2.